2017
DOI: 10.1111/apt.14428
|View full text |Cite
|
Sign up to set email alerts
|

Generic daclatasvir plus sofosbuvir, with or without ribavirin, in treatment of chronic hepatitis C: real‐world results from 18 378 patients in Egypt

Abstract: Real-world experience of generic SOF-DCV in patients with chronic HCV-G4 proved to be safe and associated with a high SVR12 rate, in patients with different stages of fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
72
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 39 publications
7
72
2
Order By: Relevance
“…A patient was considered eligible for the study when he or she met the following criteria according to the protocol of Egyptian Ministry of Health: HCV‐ribonucleic acid (RNA) positive. Age ≥18 years, while patients ≥65 years performed a cardiology assessment prior to therapy by ECG and echocardiography before recruitment to the study. Only easy‐to‐treat HCV patients were included in the study, and they had all of the following criteria: (according to The National Committee for Control of Viral Hepatitis (NCCVH) Treatment naïve patients Total bilirubin ≤1.2 mg/dL Serum albumin ≥3.5 g/dL International normalized ratio (INR) ≤1.2 Platelet count ≥150,000/mm 3 …”
Section: Methodsmentioning
confidence: 99%
“…A patient was considered eligible for the study when he or she met the following criteria according to the protocol of Egyptian Ministry of Health: HCV‐ribonucleic acid (RNA) positive. Age ≥18 years, while patients ≥65 years performed a cardiology assessment prior to therapy by ECG and echocardiography before recruitment to the study. Only easy‐to‐treat HCV patients were included in the study, and they had all of the following criteria: (according to The National Committee for Control of Viral Hepatitis (NCCVH) Treatment naïve patients Total bilirubin ≤1.2 mg/dL Serum albumin ≥3.5 g/dL International normalized ratio (INR) ≤1.2 Platelet count ≥150,000/mm 3 …”
Section: Methodsmentioning
confidence: 99%
“…[22][23][24][25][26] Several studies carried out in Egyptian adults with HCV infection showed similar results. [27][28][29][30][31][32] The aim of this study was to investigate the safety and efficacy of combined therapy with SOF and DCV in HCV GT-4 chronic infection in children aged 8 to 18 years or weighing 17 kg or more.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a study in younger children 3-11 years of age with genotypes 2 and 3 treated with SOF + Ribavirin is ongoing until April 2018 and is yet to release its results (NCT02175758).Several previous studies revealed high efficacy of SOF/DCV based treatments in adults across different genotypes and subpopulation groups, including treatment-naïve, treatment experienced, cirrhotic, non-cirrhotic, HIV-coinfected and post-transplant patients, with at least 12-week long regimens resulting in SVR12 rates ranging from 84.54 to 98% [22][23][24][25][26][27][28][29][30][31][32]. There have thus far only been two published studies of SOF/DCV use in adolescents.…”
mentioning
confidence: 99%
“…The increasing prestige of the journal is reflected in the most recent increase in our impact factor (IF); during 2019, our 2‐year IF increased from 7.357 to 7.731 ranking AP&T in 11th place among 84 journals in gastroenterology and hepatology. The 10 papers published during 2018 that were the most highly cited during 2019 included such diverse topics as the epidemiology of Helicobacter pylori infection, the intestinal mirobiome and dysbiosis, biologic agents for IBD and evolving treatments for chronic viral hepatitis.…”
mentioning
confidence: 99%